2017
DOI: 10.1016/j.tjog.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of umbilical cord arterial blood lactate and pH values for predicting short-term neonatal outcomes

Abstract: Umbilical cord arterial lactate and pH predicted short-term neonatal outcomes with similar efficacies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 17 publications
3
17
0
Order By: Relevance
“…36 Many similar studies have observed that both cord blood lactate and pH had almost equal significance in prediction of overall neonatal outcome. 35,40 Hence, Umbilical cord arterial blood pH and LDH levels were significantly associated with poor Apgar score of newborns at birth and correlates well with NICU admission, neonatal complications and deaths in women with hypertensive disorders of pregnancy.…”
Section: Tablementioning
confidence: 84%
“…36 Many similar studies have observed that both cord blood lactate and pH had almost equal significance in prediction of overall neonatal outcome. 35,40 Hence, Umbilical cord arterial blood pH and LDH levels were significantly associated with poor Apgar score of newborns at birth and correlates well with NICU admission, neonatal complications and deaths in women with hypertensive disorders of pregnancy.…”
Section: Tablementioning
confidence: 84%
“…Our inclusion criteria were full-term neonates admitted to the NICU during their rst 6 hours of life and met the diagnostic criteria speci ed by (AAP) [8] which are: base de cit > 10, APGAR scores ≤ ve at 10 minutes with a continued need for resuscitation, Metabolic acidosis with pH < 7.0, and Presence of primary or secondary apnea. On the other hand, we excluded every neonate aged older than 1 day, or born with any errors such as: errors of metabolism, genetic disorders, congenital neurologic disorders, or medication effect.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…As a result of hypoxia and tissue hypo-perfusion, the regular energy requirement cannot be sustained from aerobic metabolism, so that tissues go through anaerobic metabolism to get their energy requirement and hence, it re ects the increase in the production and accumulation of lactate in blood which in turn can detect tissue hypoxia at a very early stage [7].…”
Section: Introductionmentioning
confidence: 99%